A 20‐year scoping review of the veterinary interventional radiology and interventional endoscopy literature (2000‐2019) - Nina Samuel; Michelle A. Giuffrida; William T. N. Culp; Carrie A. Palm (Journal of Veterinary Internal Medicine, 2023)
Abstract Background Interventional radiology (IR) and interventional endoscopy (IE) have broad potential for minimally invasive therapy in veterinary patients, but the scope of original peer‐reviewed veterinary IR/IE research publications has not been described. Objectives Catalogue published applications and indications for noncardiac therapeutic IR/IE in animals and describe type and quality of veterinary IR/IE research over 20 years. Methods Highly‐cited veterinary journals were searched to identify articles published 2000 to 2019 involving therapeutic IR/IE applications for clinical veterinary patients. Articles were assigned a level of evidence (LOE) according to published standards. Authorship, animal data, study design, and interventions were described. Change in publication rate, study size, and LOE of IR/IE articles over time was analyzed. Results One hundred fifty‐nine of 15 512 (1%) articles were eligible, including 2972 animals. All studies were low LOE and 43% were case reports with ≤5 animals. Number of IR/IE articles per year (P < .001), proportion of journals' articles pertaining to IR/IE (P = .02), and study size (P = .04) all increased over time, but LOE (P = .07) did not. Common target body systems were urinary (40%), digestive (23%) respiratory (20%), and vascular (13%). Common indications were nonvascular luminal obstructions (47%), object retrieval (14%), and congenital anomalies (13%). Most procedures involved indwelling medical devices or embolic agents, whereas tissue resection and other procedures were less common. Procedures utilized fluoroscopy (43%), endoscopy (33%), ultrasound (8%), digital radiography (1%), or fluoroscopy in combination with other modalities (16%). Conclusions Treatments involving IR/IE have wide applicability in veterinary medicine but large, rigorous, and comparative studies describing these procedures are lacking.